Cultivation of Japanese Mushroom Shiitake in India - Shukla, A. N. (Indian Forester, 1994)
Experiments done on the cultivation trials of Japanese Shiitake (Lenlinus edodes)mushroom in India are discussed. Success crop was obtained on the logs of Oak placed at Solan after one and half years of inoculation. This is the first report of cultivation of this mushroom in India.